Group cohesion and relatedness as predictors of self-determined motivation and burnout in adolescent female athletes - Pacewicz, C. E.; Smith, A. L.; Raedeke, T. D. (Psychology of Sport and Exercise, 2020)
Highlights • Task and social cohesion positively predicted perceived relatedness with teammates. • Relatedness with teammates positively predicted self-determined motivation. • Cohesion predicted burnout via relatedness and self-determined motivation . • Task cohesion also directly and negatively predicted athlete burnout. • The supported model suggests greater team cohesion links to less athlete burnout.